Can Erase Montage Traces Permanently in Audio Files - Karakoc, Mehmet Mehdi; Varol, Asaf (Ieee, 2018)
Sound montage is used not only for the music and film industry, but also for criminal cases. The goal is sometimes to hide the crime and sometimes to blame the innocent. The montage always leaves some marks behind. In this study, the methods used to detect these traces are summarized and it is debated whether these traces can be completely erased. Since the sound signals can be considered periodically, they can be expressed by the Fourier series. Since the continuity of the cutting process will be deteriorated, a Gibss effect occurs and can be detected in a visual analysis. Background noise and acoustics are also used to detect the mounting in auditory analysis. The detection success rate is close to 100%. But sometimes the expert's fatigue, inexperience or carelessness and some montage tracks may not be detected.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: Montage Traces; Forensic Phonetic; Digital Forensics; Montage Detection; Gibss Effect